A trial sequential meta-analysis of IFN-γ +874 A>T (rs2430561) gene polymorphism and extrapulmonary tuberculosis risk. (May 2019) - Mandal, Raju K.; Wahid, Mohd; Jawed, Arshad; Dar, Sajad A.; Panda, Aditya K.; Akhter, Naseem; Lohani, Mohtashim; Mishra, B.N.; Khan, Saif; Areeshi, Mohammed Y.; Haque, Shafiul
Abstract: Interferon-γ ( IFN -γ) plays a crucial role in immunological responses against Mycobacterium tuberculosis ( M.tb ) infection. The polymorphism at +874 A > T (rs2430561) influences the levels of IFN-γ, which may further influence the susceptibility to extrapulmonary tuberculosis (EPTB). This polymorphism has been investigated with respect to EPTB occurrence in different populations and provided contradictory and conflicting results. This study was performed to meta-statistically analyze the data and draw a more accurate conclusion regarding the association of IFN -γ +874 A > T gene polymorphism and EPTB susceptibility. A quantitative synthesis was executed for the pertinent studies retrieved from online web-databases viz. Google Scholar, PubMed/Medline and EMBASE. The pooled odds ratios (ORs) and confidence intervals (95% CIs) were estimated for all the genetic models by meta-analysis. A total of eight studies were retrieved which included 762 confirmed EPTB cases and 1341 controls. The meta-analysis results revealed reduced association of EPTB in allelic contrast (T vs. A: p = 0.001; OR = 0.668, 95% CI = 0.524 to 0.850), homozygous (TT vs. AA: p = 0.017; OR = 0.450, 95% CI = 0.234 to 0.868), heterozygous (AT vs. AA: p = 0.004; OR = 0.574, 95% CI = 0.395 to 0.835), dominant (TT + AT vs. AA: p = 0.003; OR = 0.536, 95% CI = 0.354 to 0.810) and recessive (TT vs. AA + AT: p = 0.039; OR = 0.662, 95% CI = 0.448 to 0.980) genetic models. Furthermore, re-sampling statistics also revealed reduced risk of EPTB in overall population and Asian subgroup. This meta-analysis concluded that IFN -γ +874 A > T gene polymorphism is meaningfully related with the reduced EPTB risk in overall and Asian population, and further necessitates larger studies to be conducted on this topic in other races. Highlights: Interferon-γ ( IFN -γ) plays a crucial role in tuberculosis (TB) infection. IFN -γ +874A > T (rs2430561) influences IFN-γ level & modulate extrapulmonary TB risk. IFN -γ +874A > T SNP & EPTB risk link was checked by trial sequence meta-analysis. Reduced risk of EPTB was found w.r.t. IFN -γ +874A > T SNP for overall & Asian population. Re-sampling statistics revealed reduced EPTB risk for overall and Asian population.